Separation of Judiciary from Executive: A Plea for Revision of Dictums by Superior Courts - Dr. Usman Quddus (Journal of Peace, Development and Communication, 2021)
The paper aims to critically review the law laid down by superior judiciary of Pakistan separating judiciary from the executive. The purpose is to consider restoration of executive magistracy with checks and balances. Also to consider appointments or elevation of competent judges from all walks of life in view of the failing justice system and consequently deteriorating law and order situation in the country. The methodology adopted is mainly doctrinal and critical analysis of case law jotted down by superior judiciary. The findings of the research paper beckon restoration of judges from the executive in Pakistan along-with consideration of competent adjudicators from other walks of life like executive or academicians etc. The implications of the research have huge ramification in restoring of law and order in addition to justice system of Pakistan. Such an exercise in the form of research paper to the humble knowledge of authors has not been taken before.